2022
DOI: 10.1080/17439884.2022.2141253
|View full text |Cite
|
Sign up to set email alerts
|

Highly cited educational technology journal articles: a descriptive and critical analysis

Abstract: Citations are valuable capital in the academy as the number of citations is the most frequently used indicator in evaluating the quality of papers, journals, researchers, and universities. Thus, the characteristics of highly cited articles (HCA) have become a common research topic but the approach has been mainly descriptive with no profound critical reflection of what kind of research is cited, where the research is from, where the research is published, and what do these things mean for edtech research. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…This rapid increase reflects an increasing concern about outbreak-related mental health [ 38 ]. In this context, citations are a valuable asset in academia because the number of citations is the most commonly used measurement to assess the quality of papers, journals, researchers, and universities [ 39 ]. According to our findings, journal articles are the most commonly published document type; these findings are in agreement with those of other studies [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This rapid increase reflects an increasing concern about outbreak-related mental health [ 38 ]. In this context, citations are a valuable asset in academia because the number of citations is the most commonly used measurement to assess the quality of papers, journals, researchers, and universities [ 39 ]. According to our findings, journal articles are the most commonly published document type; these findings are in agreement with those of other studies [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the research designs adopted by the included studies appeared balanced and reflected the standpoint of authors who believe there is a growing recognition of a balance in research approaches used in educational technology research (Bailey, 2014;West & Borup, 2014). However, the debate regarding the most effective design for educational technology interventions is far from settled (Jou et al, 2016;Mertala et al, 2022). The debate has to be elevated by developing a critical approach to evaluate the strengths and weaknesses of various designs for effective interventions.…”
Section: Conclusion and Implications For Further Researchmentioning
confidence: 99%
“…Recently Mertala et al (2022) made a descriptive and critical analysis of highly cited educational technology articles. They observed that in high impact factor journals by major publishers it is easier to publish positive than critical findings of the use of technology in education.…”
Section: Remarks On the Use Of Technology In Mathematics Education Pa...mentioning
confidence: 99%